Characterization of Staphylococcus aureus plasmids introduced by transformation into Bacillus subtilis. - Gryczan, T J (1978)
Covalently closed circular DNA from five Staphylococcus aureus plasmids has been introduced into Bacillus subtilis. Four of these plasmids (pUB110, pCM194, pSA2100, and pSA0501) have been selected for further study. These plasmids replicate as multicopy autonomous replicons in both Rec+ and Rec- B. subtilis strains. They may be transduced between B. subtilis strains or transformed at a frequency of 10(4) to 10(5) transformants per microgram of DNA. The molecular weights of these plasmids were estimated, and restriction endonuclease cleavage site maps are presented. Evidence is given that pSA2100, an in vivo recombinant of pSA0501 and pCM194 (S. Iordănescu, J. Bacteriol. 124:597-601, 1975), arose by a fusion of the latter plasmids, possibly by insertion of one element into another as a translocatable element. Genetic information from three other S. aureus plasmids (pK545, pSH2, and pUB101) has also been introduced into B. subtilis, although no covalently closed circular plasmid DNA was recovered.